Écrire la différence : une relecture politique des nouvelles de Sylvia Plath - Federica DORIA (E-REA)
This article proposes a feminist reading of Johnny Panic and the Bible of Dreams and Other Prose Writings (1977) by Sylvia Plath. Its main purpose is to deconstruct Ted Hughes’ critical analysis of Plath’s stories which claims their aesthetic « weakness » (« Introduction », Johnny Panic). Moreover, this paper analyzes a selection of Plath’s stories by showing their political dimension and their connections with several concepts of the sexual difference feminism. In conclusion, this article retraces the evolution of Plath’s political awareness as well as her new interest in History and in her contemporary socio-political world.